Self-Reported Changes in Dietary Calcium and Energy Intake Predict Weight Regain following a Weight Loss Diet in Obese Women , - Ochner, Christopher N. (2007)
This study examined relationships between changes in dietary calcium intake, energy intake, and body weight following a weight loss diet. One hundred three overweight or obese women lost weight over 22 wk. Dietary calcium and energy intake were assessed using the Block 98 FFQ (Block) and 5-d food records (FR) at intervention end and 6- and 18-mo follow-up. Pearson correlations were used to relate changes in dietary calcium to energy intake. We used regression analyses to examine relationships between changes in dietary calcium, energy intake, and weight regain. Changes in dietary calcium and energy intake were correlated (r = 0.32; P = 0.033), but neither variable alone predicted weight regain. From 6- to 18-mo follow-up, greater dietary calcium intake inversely predicted weight regain when controlling for changes in energy intake (P = 0.048 Block and 0.025 FR), whereas higher energy intake positively predicted weight regain when controlling for changes in dietary calcium intake (P = 0.009 Block and 0.049 FR) (combined R² = 0.153 Block and 0.178 FR). Dietary calcium may oppose weight regain, reducing the effect of greater energy intake. Our results encourage future research on the potential relationship between dietary calcium and weight loss maintenance and suggest that controlling for dietary calcium may increase the ability of energy intake to predict weight change.